A note on Crude Protein and Gum Production of Two Varieties of Guar [Cyamopsis tetragonolobe(Linn.) Taub.] as influnced by differne t seed rates and row spacings. - Singh, Dharam Pal; Rathore, D N; Singh, Harbir; Singh, Vijay (Annals of Arid Zone, 2016)
.